DETERMINATION OF ALTERNATIVE TECHNOLOGICAL FACTORS FOR THE PRODUCTION OF FUNCTIONAL FABRIC WITH A COMPLEX STRUCTURE - KHAMRAEVA, SEVARAXON; КADIROVA , DILFUZA; DAVLATOV, BEХZOD (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article reflects the research results on identifying alternative technological factors for producing functional fabrics with a complex structure on modern electronic weaving looms. New fabric samples with functional variable layers were developed on the Somet Thema Super Excel-190 (Italy) loom. For weaving experimental fabric samples, 100% cotton 25x2 tex linear density yarns were used as the body, and 50% cotton + 50% modal mixed yarns were used as the warp. Alternating fabric layers have a structure of a 6:1 ratio, in fabric formation in the loom, a six-layer part is formed, and then a single-layer part of the fabric is formed. This ratio of layers creates bumps and grooves on the surface of the fabric, which allows the bed to provide air exchange and moisture transfer for the patient, dry the product, and have massage properties due to the bumps and grooves. The air permeability of the fabric was selected as the main output factor for the alternative of the weaving process of the complex structure fabric on the loom.